2022
DOI: 10.3389/fmicb.2022.863129
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation of Acinetobacter baumannii isolates from bloodstream infections in a tertiary-level hospital in South Africa

Abstract: Acinetobacter baumannii is an opportunistic pathogen and causes various infections in patients. This study aimed to describe the clinical, epidemiological and molecular characteristics of A. baumannii isolated from BCs in patients at a tertiary-level hospital in South Africa. Ninety-six isolates from bloodstream infections were collected. Clinical characteristics of patients were recorded from patient files. Organism identification and AST was performed using automated systems. PCR screening for the mcr-1 to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Data providing information on the epidemiology of colistin-resistant A. baumannii are generally shown by MLST categorization (Oxford and Pasteur) of these isolates [ 151 , 152 ]. According to the less discriminating Pasteur scheme, colistin-resistant A. baumannii sequence type (ST) 2 isolates are found to be most prevalent ST associated with colistin resistance in A. baumannii and occur in all continents for which data are available (Europe, Asia, Africa, and North and South America) [ 73 , 74 , 75 , 76 , 86 , 88 , 89 , 90 , 91 , 97 , 107 , 153 , 154 , 155 ] ( Figure 2 ). In addition, ST1 was detected in Europe and Africa [ 90 , 95 , 97 , 154 , 156 ], whereas other Pasteur STs occurred exclusively in specific continents (Europe—ST195, ST345, ST490, ST492, ST537, ST632, ST636, ST745, ST1421, and ST1816; Asia—ST1303; Africa—ST158 and ST570; North America—ST46 and ST94; South America—ST15, ST25, ST79, and ST730) [ 74 , 76 , 86 , 88 , 89 , 92 , 97 , 116 , 128 , 129 , 130 , 157 ] ( Figure 2 ).…”
Section: Epidemiology Of Colistin-resistant a Baumanniimentioning
confidence: 99%
See 2 more Smart Citations
“…Data providing information on the epidemiology of colistin-resistant A. baumannii are generally shown by MLST categorization (Oxford and Pasteur) of these isolates [ 151 , 152 ]. According to the less discriminating Pasteur scheme, colistin-resistant A. baumannii sequence type (ST) 2 isolates are found to be most prevalent ST associated with colistin resistance in A. baumannii and occur in all continents for which data are available (Europe, Asia, Africa, and North and South America) [ 73 , 74 , 75 , 76 , 86 , 88 , 89 , 90 , 91 , 97 , 107 , 153 , 154 , 155 ] ( Figure 2 ). In addition, ST1 was detected in Europe and Africa [ 90 , 95 , 97 , 154 , 156 ], whereas other Pasteur STs occurred exclusively in specific continents (Europe—ST195, ST345, ST490, ST492, ST537, ST632, ST636, ST745, ST1421, and ST1816; Asia—ST1303; Africa—ST158 and ST570; North America—ST46 and ST94; South America—ST15, ST25, ST79, and ST730) [ 74 , 76 , 86 , 88 , 89 , 92 , 97 , 116 , 128 , 129 , 130 , 157 ] ( Figure 2 ).…”
Section: Epidemiology Of Colistin-resistant a Baumanniimentioning
confidence: 99%
“…MLST typing according to the Oxford scheme revealed that some STs of A. baumannii resistant to colistin are distributed across different continents: ST92 (Asia and North America) [ 101 , 158 ], ST195 (Europe and Africa) [ 76 , 154 ], ST208 [ 76 , 86 , 90 , 97 ] and ST281 [ 75 , 86 , 97 ] (Europe and North America), and ST451 (Europe, Asia, and North America) [ 86 , 90 , 97 , 139 , 158 ] ( Figure 2 ). Interestingly, ST208 has been suggested to be identical to ST92, with the typing result depending on the sequencing performed (high-throughput or Sanger, respectively) [ 86 ].…”
Section: Epidemiology Of Colistin-resistant a Baumanniimentioning
confidence: 99%
See 1 more Smart Citation
“…Acinetobacter baumannii therapy is typically problematic ( 11 ) and is further worsened by the increasing rates of resistance to carbapenems, with high resistance rates of up to 100% reported globally ( 12 15 ). Carbapenem resistance in A. baumannii is encoded primarily by bla OXA-23 genes, which are more common among the globally disseminated clones and are frequently mobilized and spread between different strains via plasmids ( 3 , 8 , 16 ).…”
Section: Introductionmentioning
confidence: 99%